The Use of Fluorescein Angiography to Evaluate Pediatric Abusive Head Trauma: An Observational Case Series. (September 2017) - Tran, Kimberly D.; Ko, Audrey C.; Read, Sarah P.; Reyes-Capó, Daniela; Negron, Catherin I.; Fallas, Brenda J.; Tutiven, Jacqueline; Berrocal, Audina M.
Background or Purpose: The evaluation of retinal hemorrhages in the setting of suspected abusive head trauma (AHT) has important medical, social, and legal implications. Challenges include late presentation after retinal hemorrhages have resolved and differentiating AHT-related retinal changes from mimicking pathologies. To date, angiographic evidence of peripheral retinal injury in AHT has been reported in small series, but further study is needed to determine the prevalence and long-term sequelae of these findings. The purpose of this study was to describe fluorescein angiography (FA) findings in pediatric patients with a history of definite AHT and demonstrate the potential utility of FA in evaluating cases of suspected abuse with late presentation. Methods: Retrospective case series of 10 eyes in 5 pediatric patients with a history of definite AHT. RetCam fundus photography images and digital FA were performed. Results: Peripheral retinal nonperfusion affected 10 of 10 eyes in patients with a history of definite AHT. These changes persisted after acute retinal hemorrhages had resolved. Conclusions: "Retinal surveys" using FA provide angiographic evidence of peripheral retinal nonperfusion that may be a sign of AHT. This series adds to the growing body of cases reporting similar AHT-related findings and additionally demonstrates the longevity of these pathologic changes after trauma, which has not been previously described. Fluorescein angiography may offer a distinct advantage in evaluating cases of suspected abuse with late presentation to medical care when pathognomonic retinal hemorrhages may no longer be present. Further study is needed to determine the prevalence and long-term sequelae of these findings.